Reconstruction of ice stream retreat and palaeoceanographic development during the deglaciation and Holocene in the Storfjorden Trough, Svalbard. Based on geophysical data, benthic foraminiferal and sedimentological records - Lockwood, Christine Joanne (UiT Norges arktiske universitet, 2016)
Here we investigate the retreat of a palaeo-ice stream and the subsequent palaeoceanographic development in the eastern Storfjorden Trough during the deglaciation and Holocene. The results are based on multibeam bathymetric and acoustic sub-bottom data, and a multiproxy analysis of a 14C dated sediment core (including benthic foraminifera, δ13C, δ18O and sedimentology). The ice stream experienced a rapid retreat with a still-stand of the grounding line leading to the deposition of a glacial sediment lobe (<14,000 cal. years). Atlantic Water has continuously been present in the eastern Storfjorden Trough since the Allerød interstadial, following the rapid retreat of the ice stream and onset of glaciomarine sedimentation (c. 13,800 cal. years). The Younger Dryas (c. 12,700 cal. years) and late Holocene (c. 4000 cal. years) were identified as cold periods characterised by reduced Atlantic Water inflow and extensive sea ice cover. Warmer periods in the early Holocene (c. 9000 cal. years) and mid-Holocene (after c. 8200 cal. years) were characterised by a prevalence of Atlantic Water. The reconstruction of the retreat of the palaeo-ice stream and palaeooceanographic development presented gives a further understanding of the dynamic responses of ice-ocean interactions to past climatic changes. Keywords Palaeoceanography; deglaciation; ice stream; retreat; Atlantic Water; Arctic water; Storfjorden; benthic foraminifera; oxygen isotopes; carbon isotopes. Keywords Palaeoceanography; deglaciation; ice stream; retreat; Atlantic Water; Arctic water; Storfjorden; benthic foraminifera; oxygen isotopes; carbon isotopes.